How to Reduce Physical Inactivity in School Context? a Systematic Review of the Concept of Body Practices - Soto-Lagos, R (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
(1) Background: Physical inactivity is a recognized global problem, with schools identified by UNESCO and WHO as critical settings for intervention. Despite existing efforts, the prevalence of physical inactivity remains high. This study aims to explore the potential of the concept of body practices as a novel framework to address physical inactivity within school contexts, potentially offering an alternative to traditional intervention models. (2) Methods: This study carried out a systematic review of the concept of body practices to understand its use in the scientific literature. (3) Results: The results indicate that (a) the definition of the concept that the authors used is broad; (b) the problems they face are varied, such as the life cycle, negative emotions, gender, physical inactivity, well-being, and social problems; (c) the research methodologies are predominantly quantitative; (d) and the intervention in schools focuses on students, but not on the entire school community. (4) Conclusions: this concept has great potential for use in initiatives and/or policies that seek to address physical inactivity in the school context. © 2024 by the authors.